DETERMINATION OF THE AGE OF LOW-MASS CLOSE BINARY STARS OF EARLY SPECTRAL CLASSES - Bondarenko, I. I.; Perevozkina, E. L. (Одеські астрономічні публікації, 2017)
The results of the determination of age of less-massive close binary stars of the early spectral classes are presented.